Development of an optimized cell-based selection system for phage display libraries - Czarnecka, Malgorzata; Findik, Nicole; Schlör, Anja; Hanack, Katja (Biology methods and protocols, 2025)
The discovery of antibodies through phage display is significantly influenced by antigen presentation during panning, particularly for membrane-anchored proteins, which pose challenges due to their complex structures. Traditional approaches, such as whole cells expressing the target protein, often result in low antigen density and high background signals. In this study, we describe an alternative method using stably transfected cell lines that express the target antigen on their surface, regulated by an intracellular enhanced green fluorescent protein (EGFP) signal. This system enables high-throughput flow cytometry-based screening of phage display libraries to isolate human antibodies that recognize the native conformation of membrane proteins. Using human epithelial cell adhesion molecule (EpCAM) and human neuroplastin 65 (NP65) as model antigens, we established an optimized screening workflow with polyclonal phage pools. Selected EpCAM-specific single-chain variable fragments (scFvs) from a naïve library were recombinantly expressed with an IgG4 scaffold and characterized for specific binding. This approach provides an effective platform for the identification of antibodies against membrane proteins in their native state.